How does the audience return to the music theater? Exploring the influence of musical theater adaptation of Chinese nursery rhymes - Jian Li; Yu Hu (PLoS ONE, 2025)
Musicals, as an art form, are attracting greater attention in China’s increasingly competitive market. In particular, the adaptation of Chinese nursery rhymes in musicals and its influence on audience affective reactions and behavioral intentions has emerged as a notable research focus. This study aims to explore the impact of nursery rhyme adaptations in musicals on audience interaction, affective reactions, satisfaction, and repurchase intention. Using questionnaire surveys and structural equation modeling, we empirically analyse how audience interaction and affective reactions in these musical adaptations enhance satisfaction and increase repurchase intention. The results indicate that audience interaction significantly boosts affective reactions, leading to heightened satisfaction and a greater likelihood of repurchase. Furthermore, elements such as scenic design, lyric adaptation, and melody adaptation enrich the overall artistic experience by influencing both cognitive and affective responses. This study offers strategic recommendations for musical production, specifically highlighting the importance of audience interaction and affective reactions throughout the creative process to maximize engagement and commercial success. In conclusion, our findings provide valuable theoretical and practical insights that not only support cultural inheritance but also drive innovation within the musical theater industry.